A human secretome library screen reveals a role for Peptidoglycan Recognition Protein 1 in Lyme borreliosis - Gupta, Akash; Arora, Gunjan; Rosen, Connor E; Kloos, Zachary; Cao, Yongguo; Cerny, Jiri; Sajid, Andaleeb; Hoornstra, Dieuwertje; Golovchenko, Maryna; Rudenko, Natalie; Munderloh, Ulrike; Hovius, Joppe W; et al. (PLOS pathogens, 2020)
Lyme disease, the most common vector-borne illness in North America, is caused by the spirochete Borrelia burgdorferi. Infection begins in the skin following a tick bite and can spread to the hearts, joints, nervous system, and other organs. Diverse host responses influence the level of B. burgdorferi infection in mice and humans. Using a systems biology approach, we examined potential molecular interactions between human extracellular and secreted proteins and B. burgdorferi. A yeast display library expressing 1031 human extracellular proteins was probed against 36 isolates of B. burgdorferi sensu lato. We found that human Peptidoglycan Recognition Protein 1 (PGLYRP1) interacted with the vast majority of B. burgdorferi isolates. In subsequent experiments, we demonstrated that recombinant PGLYRP1 interacts with purified B. burgdorferi peptidoglycan and exhibits borreliacidal activity, suggesting that vertebrate hosts may use PGLYRP1 to identify B. burgdorferi. We examined B. burgdorferi infection in mice lacking PGLYRP1 and observed an increased spirochete burden in the heart and joints, along with splenomegaly. Mice lacking PGLYRP1 also showed signs of immune dysregulation, including lower serum IgG levels and higher levels of IFNγ, CXCL9, and CXCL10.Taken together, our findings suggest that PGLYRP1 plays a role in the host's response to B. burgdorferi and further demonstrate the utility of expansive yeast display screening in capturing biologically relevant interactions between spirochetes and their hosts.
Keywords: lymeská nemoc; Animals; cytokiny; Humans; lidé; Borrelia burgdorferi; zvířata; Cytokines; Mice; genová knihovna; myši inbrední BALB C; Lyme Disease; Mice, Inbred BALB C; Gene Library; myši